Antiviral-Resistant Fulminant Herpes Hepatitis in Pregnancy - Herrera, Christina A.; Eichelberger, Kacey Y.; Chescheir, Nancy C. (American Journal of Perinatology Reports, 2013)
Fulminant herpes hepatitis with disseminated extrahepatic involvement in pregnancy is rare and carries a high mortality risk. Although acyclovir remains standard first-line therapy, effective management of acyclovir-resistant disseminated herpes simplex virus (HSV) in pregnancy remains elusive. We present a case of disseminated HSV resistant to both acyclovir and foscarnet, the first double-agent resistant case in pregnancy reported in the literature to date. In this case, therapeutic delivery was the ultimate treatment resulting in full recovery.
Keywords: herpes hepatitis; fulminant herpes; pregnancy herpes; disseminated herpes